1991
DOI: 10.1172/jci115323
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional characterization of human ventricular myofiber architecture by ultrasonic backscatter.

Abstract: Normal human left ventricular architecture comprises a highly aligned array of cardiac myofibers whose orientation depends on transmural location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 32 publications
1
26
1
3
Order By: Relevance
“…The anisotropic structure of the LV wall, with fiber directions changing from a right-handed helix in the subendocardium to a left-handed helix in the subepicardium ( Fig. 2A), alters the propagation and backscatter of ultrasonic waves (31)(32)(33). Previous investigations have shown that the integrated backscatter in the LV wall varies approximately as a sinusoidal function of the angle of insonification at each transmural level (31,34).…”
Section: Effect Of Myocardial Anisotropy On Appearance Of Cardiac Ultmentioning
confidence: 94%
See 2 more Smart Citations
“…The anisotropic structure of the LV wall, with fiber directions changing from a right-handed helix in the subendocardium to a left-handed helix in the subepicardium ( Fig. 2A), alters the propagation and backscatter of ultrasonic waves (31)(32)(33). Previous investigations have shown that the integrated backscatter in the LV wall varies approximately as a sinusoidal function of the angle of insonification at each transmural level (31,34).…”
Section: Effect Of Myocardial Anisotropy On Appearance Of Cardiac Ultmentioning
confidence: 94%
“…2A), alters the propagation and backscatter of ultrasonic waves (31)(32)(33). Previous investigations have shown that the integrated backscatter in the LV wall varies approximately as a sinusoidal function of the angle of insonification at each transmural level (31,34). Greater backscatter resulting in a brighter image area is observed when fibers are interrogated by an ultrasound beam that is approximately perpendicular rather than parallel to the direction of the fibers.…”
Section: Effect Of Myocardial Anisotropy On Appearance Of Cardiac Ultmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound can also be used to characterize the myocardial structure, through the analysis of backscattered ultrasound. The dependence of backscattered intensity and ultrasound attenuation with fiber orientation was investigated extensively over the past decades [17][18][19][20]. Nevertheless, backscattered intensity depends on many parameters including heterogeneity of the material, presence of bright specular echoes, angle view and period in the cardiac cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have described phenomena that are related or potentially related to myocardial ultrasonic integrated backscatter and its variation during the cardiac cycle (Barzilai et al 1984;Glueck et al 1985;Hoffmeister et al 1991;Maderas et al 1988;Mottley and Miller 1988;Mottley et al 1984;Recchia et al 1993Recchia et al , 1995Sagar et al 1987Sagar et al , 1988Sagar et al , 1990Wear et al 1986Wear et al , 1989Wickline et al 1985aWickline et al , 1985bWickline et al , 1991Wickline et al , 1992). An important observation has been the empirical inverse linear relation between wall thickness and integrated backscatter (Rijsterborgh et al 1990van der Steen et al 199 1) , This relation does not seem to hold in all cases (Milunski et al 1989a(Milunski et al , 1989b.…”
Section: Discussionmentioning
confidence: 99%